A single-molecule view of the assembly pathway, subunit stoichiometry and unwinding activity of the bacteriophage T4 primosome (helicase-primase) complex - Lee, Wonbae (2013)
Single molecule fluorescence resonance energy transfer (smFRET) methods were used to study the assembly pathway and DNA unwinding activity of the bacteriophage T4 helicase-primase (primosome) complex. The helicase substrates used were surface-immobilized model DNA replication forks ‘internally’ labeled in the duplex region with opposed donor/acceptor (iCy3/iCy5) chromophore pairs in the lagging and leading strands. The time-dependence of the smFRET signals was monitored during the unwinding process and helicase rates and processivities were measured as a function of GTP concentration. This smFRET approach was also used to investigate the subunit stoichiometry of the primosome and the assembly pathway required to form functional and fully active primosome-DNA complexes. We confirmed that gp41 helicase monomer subunits form stable hexameric helicases in the presence of GTP and that the resulting (gp41)(6) complexes bind only weakly at DNA fork junctions. The addition of a single subunit of gp61 primase stabilized the resulting primosome complex at the fork and resulted in fully active and processive primosome helicases with gp41:gp61 subunit ratios of 6:1, while higher and lower subunit ratios substantially reduced the primosome unwinding activity. The use of alternative assembly pathways resulted in loss of helicase activity and formation of metastable DNA-protein aggregates, which were easily detected in our smFRET experiments as intense light-scattering foci. These single molecule experiments provide a detailed real time visualization of the assembly pathway and duplex DNA unwinding activity of the T4 primosome and are consistent with more indirect equilibrium and steady state results obtained in bulk solution studies.